PRACTICAL ASPECTS OF PRACTICAL ASPECTS OF COOPERATION BETWEEN THE STATE BORDER GUARD OF LATVIA AND FEDERAL SECURITY SERVICE BORDER GUARD SERVICE OF RUSSIAN FEDERATION - Kuprijanova, Jekaterina; Livdāns, Juris; Arbidāne, Iluta (Border Security and Management, 2016)
One of the main State Border Guard priorities is to maintain and develop the state border guarding system, according to the European Union external borders requirements, by fulfilling the conditions of the Schengen acquis. Schengen acquis provides that international cooperation in the field of border security can have multilateral, bilateral and local dimensions. In this context, an agreements concluded with bordering countries on cooperation in the field of border management is an effective tool to strengthen border security (EU Schengen Catalogue, 2002). In research as methodology are used scientific literature in the field of international law, treaties and agreements, the law of the Republic of Latvia, the State border guard of the internal regulations and the State border guard of unpublished materials. The Republic of Latvia and the Russian Federation cooperate in the field of development and implementation of coherent measures for the border control. Cooperation with RF is executed based on treaties and agreements concluded, as well, maintaining contacts between competent representatives of both countries at various management levels. The extensive cooperation between neighbouring countries on maintenance of security at the border results in the elucidation of the incidents occurring at the state border and other relevant issues, at the same time providing stability and security at the common border.